Corn starch doped with sodium iodate as solid polymer electrolytes for energy storage applications - Fatin Farhana Awang (Acta Polytechnica, 2021)
The concern about environmental problems has inspired a of energy storage devices from natural sources. In this study, solid polymer electrolyte (SPE) films made from corn starch doped with different compositions of sodium iodate (NaIO3) were prepared via the solution casting technique. The effect of dopants on the structure, morphology and electrical properties of SPE films was analysed using X-Ray diffraction (XRD), scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS) analysis. From the XRD, it shows that the amorphous state would influence the conductivity values of SPE films. Then, the SEM observations revealed that the films seem to be rough, porous and having branch structure, which may affect the conductivity of SPE films. The maximum conductivity of SPE film is obtained from 3 wt.% of NaIO3 with a value of 1.08 × 10−4 Scm−1 at room temperature (303K). From the results, this SPE is proposed to have a great potential in future energy storage applications.